Chronic inflammatory pain promotes place preference for fentanyl in male rats but does not change fentanyl self-administration in male and female rats. (15th June 2023) - Barattini, Angela E.; Montanari, Christian; Edwards, Kimberly N.; Edwards, Scott; Gilpin, Nicholas W.; Pahng, Amanda R.
Abstract: The current opioid epidemic is a national health crisis marked by skyrocketing reports of opioid misuse and overdose deaths. Despite the risks involved, prescription opioid analgesics are the most powerful and effective medications for treating pain. There is a clear need to investigate the risk of opioid misuse liability in male and female adults experiencing chronic pain. In the present study, we tested the hypothesis that chronic inflammatory pain would increase fentanyl intake, motivation to acquire fentanyl, and drug seeking in the absence of fentanyl in rats. Fentanyl intake, motivation for fentanyl, and drug seeking were tested under limited and extended access conditions using intravenous fentanyl self-administration. Fos activity in ventral tegmental area (VTA) dopamine neurons following intravenous fentanyl challenge (35 μg/kg) was examined using immunohistochemistry. Finally, we tested whether low-dose fentanyl supports development of conditioned place preference under an inflammatory pain state in rats. Contrary to our hypothesis, fentanyl self-administration and VTA Fos activity were unaffected by inflammatory pain status. During acquisition, males exhibited increased fentanyl intake compared to females. Animals given extended access to fentanyl escalated fentanyl intake over time, while animals given limited access did not. Males given extended access to fentanyl demonstrated a greater increase in fentanyl intake over time compared to females. During the dose-response test, females given limited access to fentanyl demonstrated increased motivation to acquire fentanyl compared to males. Both sexes displayed significant increases in responding for fentanyl as unit fentanyl doses were lowered. Following fentanyl challenge, females exhibited higher numbers of Fos-positive non-dopaminergic VTA neurons compared to males. Using conditioned place preference, we found that chronic inflammatory pain promotes fentanyl preference in males, but not females. These findings suggest that established fentanyl self-administration is resistant to change by inflammatory pain manipulation in both sexes, but chronic inflammatory pain increases the rewarding properties of low-dose fentanyl in males. Highlights: Male and female rats given extended access to fentanyl escalate use over time. LgA males demonstrate a greater increase in fentanyl intake than LgA females. ShA females demonstrate increased motivation to acquire fentanyl compared to ShA males. Inflammatory pain promotes fentanyl preference but does not change fentanyl intake. Following fentanyl challenge, female rats have more Fos + VTA neurons than males.